1990
DOI: 10.1038/344245a0
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of tumour necrosis factor for development of silica-induced pulmonary fibrosis

Abstract: The deposition of silica particles in the lung of man or experimental animals leads to silicosis, a disease of progressive respiratory failure caused by a fibrotic reaction. It has long been suspected that the phagocytosis of silica by pulmonary macrophages induces the secretion of fibrogenic factors. Several potentially fibrogenic cytokines released by macrophages have been identified, including interleukin-1 (IL-1), tumour necrosis factor-alpha (TNF), platelet-derived growth factor, basic fibroblast growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
312
2
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(330 citation statements)
references
References 19 publications
15
312
2
1
Order By: Relevance
“…As shown by studies performed in experimental models [5] or in patients with CWP [6,24], macrophages and their products, especially TNF, appear to play a key role in the development of CWP. So we studied, in vitro, the effects of AM supernatants on the expression of adhesion molecules by two different cell types: EC, and alveolar epithelial cells.…”
Section: In Vitro Expression Of Leucocyte-endothelial Cell Adhesion Mmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by studies performed in experimental models [5] or in patients with CWP [6,24], macrophages and their products, especially TNF, appear to play a key role in the development of CWP. So we studied, in vitro, the effects of AM supernatants on the expression of adhesion molecules by two different cell types: EC, and alveolar epithelial cells.…”
Section: In Vitro Expression Of Leucocyte-endothelial Cell Adhesion Mmentioning
confidence: 99%
“…Among them, TNF-is thought to be the main cytokine responsible for the development of pneumoconiotic lesions [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Piguet and coworkers (48,49) demonstrated that TNF␣ antagonists can significantly reduce the accumulation of ECM in mouse models of silica-and bleomycin-induced pulmonary fibrosis. Silica and bleomycin stimulate the expression of TNF␣ and lead to a patchy fibrosis after 15 days.…”
Section: Tnf␣ In Fibrotic Diseases 2231mentioning
confidence: 99%
“…Treatment of established fibrosis with soluble TNFRI was also effective, as demonstrated by experiments in which soluble TNFRI was administered 25 days after bleomycin and silica. Accordingly, continuous infusion of recombinant TNF␣ strongly augmented the fibrotic process (48).…”
Section: Tnf␣ In Fibrotic Diseases 2231mentioning
confidence: 99%
“…TNF-a has been implicated in the pathogenesis of asthma [1] and interstitial lung diseases [2]. It also plays an important role in both protective [3] and pathological immune responses to Gram-negative bacteria and mycobacteria [4].…”
mentioning
confidence: 99%